Discovery, characterization, and applications of cysteine-rich peptides from medicinal plants - Huang, Jiayi (Nanyang Technological University, 2020)
Medicinal plants showed great importance in managing and treating human diseases. Currently, plant-derived small-molecule metabolites with molecular weight (M.W.) <1 kDa are major active components that account for approximately 46% of all the clinically approved drugs. Another major family of pharmaceuticals that have been extensively studied and used clinically is proteins with M.W. >10 kDa. However, few peptidyl products which occupy the chemical space between metabolites and proteins are clinically approved as drugs. Typically, peptides are susceptible to harsh conditions and have poor bioavailability. Disulfide-constrained cysteine-rich peptides (CRPs) are a family of molecules with highly compact structures, in a particular range of M.W. from 2 – 6 kDa. These disulfide bridges confer them the stability against thermal, acidic and enzymatic degradation. Currently, these naturally-occurring disulfide-constrained peptides are highly under-explored in medicinal plants. Another vital issue for herbal medicines is the misidentification of plant species and the presence of adulterants. The traditional authentication method using chromatographic fingerprinting is precise, sensitive, and reproducible. However, laborious sample preparation, relatively long analytical run-times, and the large volume of organic solvents consumption in HPLC hinders its application as a high-throughput screening technique. Hence, the development of a rapid and accurate quality control method is urgently needed. My thesis aims to discover and characterize CRPs from medicinal plants and to apply them in the authentication of herbal medicines. A general and rapid method, which employs CRPs as unique chemical markers for the authentication of herbal medicines, was described in this thesis. This CRP fingerprinting method produces consistent results for herbal authentication regardless of the morphology, chemical composition, and origins of the plant species. The differentiation of two similar species, Radix Astragali and Radix Hedysarum, was used as an example to validate the method. Coupling with multivariate analyses, the study showed that CRP fingerprinting is fast, and the classification accuracy is comparable to that of the conventional authentication method using UPLC. To further understand the usefulness and functions of CRPs, clusters of CRPs discovered from medicinal plants and important crops were studied. They include CRPs from Coffea canephora and Coffea liberica, which are plants with medicinal values used to produce the second-largest commodity, coffee drinks. Proteomic and transcriptomic analyses showed that coffeetides identified from the Coffea species are nonchitin- binding hevein-like peptides. Another group of CRPs was identified from the roots of Astragalus membranaceus (Fisch.) Bje, which is a traditional Chinese medicine for improving overall vitality and treating diabetes. Two different types of CRPs were identified in this plant and designated as α- and β-astratides. NMR spectroscopy, bioinformatics analysis, and functional bioassays were used to determine the structure, evolutionary relationship, and functions of all these CRPs. Taken together, my thesis expanded the existing library of CRPs and explored their potential for drug design and their usefulness as fingerprints for the authentication of herbal medicine.